The Information Content of Ratings: An Analysis of Australian Credit Default Swap Spreads. (March 2014) - Wang, Jue; Svec, Jiri; Peat, Maurice
<x xml:space="preserve">Abstract</x> We examine the information content of Australian credit rating announcements by measuring the abnormal changes in credit default swap (CDS) spreads. CDS spreads provide a direct view of credit quality and thus should impound information quickly when investors receive new credit risk related information via a rating event. Using an event study methodology, we show that watch downs and rating upgrades contain valuable information even after controlling for sources of contamination. We find that watch downs elicit statistically significant market reactions, while subsequent downgrades are anticipated. Upgrades are associated with a significant but small abnormal reduction in CDS spreads, whereas watch ups appear to contain no new information.